Efektivitas Penggunaan Herbal Terhadap Performa Produksi Ayam Ras Petelur: Efektivitas Penggunaan Herbal terhadap Performa Produksi Ayam Ras Petelur - Suryani, Lili; Darwis, D; Nurcaya, N (Journal Galung Tropika, 2023)
Demand for poultry products continues to increase. The quality of livestock commodities is obtained by providing good feed (good feeding practices). Feed is the most significant component of production costs, namely 60-70%. Utilizing the potential of local feed ingredients can reduce feed costs and improve livestock health. Herbal administration improves livestock performance through bioactive substances. Herbs used as feed ingredients are turmeric, ginger, and indigoferas leaf meal. Herbal plants function as natural antibiotics, antivirals, and antimicrobials. This study aims to determine the effectiveness of using herbs in feed on production performance. The research location was in Mappesangka Village, Ponre District, Bone Regency, from April to December 2022. The study used a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatment consisted of basal feed (control), basal feed 97% + herbs 3%, basal feed 96% + herbs 4%, and basal feed 95% + herbs 5%. Each experimental unit consisted of 4 chickens. The strain used was the Novogen strain aged 32 weeks as many as 80 individuals, reared for 28 days. The variables observed were feed consumption, conversion, hen day production, and egg weight. The data obtained were tabulated, then statistical analysis was carried out with ANOVA and Duncan's test. The results showed that the use of herbs had a significant (P<0.05) effect on Hen Day Production (HDP). The results showed that using as much as 3% of herbs could improve laying hens' production performance.